Opening Ceremony of Odyssey: Perlis to Machu Picchu Exhibition - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
Opening Ceremony of Odyssey: Perlis to Machu Picchu Exhibition organized by Universiti Malaysia Perlis, Perpustakaan Negara Malaysia Negeri Perlis, Yayasan Tuanku Syed Putra, Embassy of Peru and Taylor's University College, 15th October 2012 was held at Dewan 2020, Kangar, Perlis, Malaysia.